2014
DOI: 10.1007/s10957-014-0656-x
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Sensing for Delay-Constrained Cognitive Radio Systems Via Convex Optimization

Abstract: Spectrum sensing is a critical issue in cognitive radio (CR) systems. When the energy of the CR system is constrained, using the energy efficiently is an important problem, which must be considered. In this paper, the energy efficiency is defined as the ratio of average spectrum efficiency of the CR system over average power consumed by the CR system. We consider a joint optimization of sensing time and power allocation to maximize the energy efficiency under the condition of sufficient protection to primary u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…10 b illustrates EE and ST as a function of sensing time for Cout=2 and Cout=4. It is well known that both ST and EE are a concave function of τs [26]. Furthermore, EE for Cout=4 is more because Pnormaltmax per each SU is less.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…10 b illustrates EE and ST as a function of sensing time for Cout=2 and Cout=4. It is well known that both ST and EE are a concave function of τs [26]. Furthermore, EE for Cout=4 is more because Pnormaltmax per each SU is less.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…In Scheme III, Particle Swarm Optimization algorithm is used for evaluating the optimal power allocation as in a previous study . In Scheme IV, the method of optimizing both sensing time and transmission power allocation is obtained by employing bisection search method as discussed in a previous study . In the proposed scheme, both IDM and EPA algorithms are used.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…EE, energy efficiency FIGURE 6 Variation of throughput against signal-to-noise ratio (SNR) for δ = 0 and δ = 0.5 FIGURE 7 Variation of energy efficiency (EE) and system throughput against the interference threshold Ith for signal-to-noise ratio (SNR) = −30 dB and −15 dB The impact of R min on the maximum energy efficiency (EE) and on the sum of transmission power for Ith = −160 dBm and Ith = −150 dBm FIGURE 9 The impact of outage threshold O th on maximum energy efficiency (EE) and throughput for Ith = −160 dBm and Ith = −150 dBm search method as discussed in a previous study. 13 In the proposed scheme, both IDM and EPA algorithms are used. It is clearly observed that our proposed scheme outperforms the other existing schemes and double threshold method performs better than the single threshold method.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations